2010
DOI: 10.4236/health.2010.212210
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of biochemical markers of fibrosis in black African patients with chronic hepatitis B

Abstract: Contradictory results of the accuracy of bio-chemical markers to predict the stage of fibrosis in black African patients with chronic hepatitis B (CHB) were previously published. We con-ducted a prospective cohort study to determine the diagnostic accuracy of aspartate ami-notransferase to platelet ratio (APRI), aspartate aminotransferase to alanine aminotransferase ratio (AAR), platelet count, age-platelet (AP) in-dex, and FIB-4 index for the prediction of sig-nificant fibrosis or cirrhosis in 117 black Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…47 The AUROC of FIB-4 for significant fibrosis was 0.733. Mahassadi et al 48 had conducted a prospective cohort study to determine the diagnostic accuracy of APRI, AAR, AP and FIB-4 index for the prediction of significant fibrosis or cirrhosis in 117 patients with chronic hepatitis B and APRI and FIB-4 index ruled out significant fibrosis with high specificity of 84.7% and 86.1%, respectively. 48 Distinguishing severe stages (F3–F4) from low or moderate stages (F0–F2) of fibrosis with high FIB-4 scores (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…47 The AUROC of FIB-4 for significant fibrosis was 0.733. Mahassadi et al 48 had conducted a prospective cohort study to determine the diagnostic accuracy of APRI, AAR, AP and FIB-4 index for the prediction of significant fibrosis or cirrhosis in 117 patients with chronic hepatitis B and APRI and FIB-4 index ruled out significant fibrosis with high specificity of 84.7% and 86.1%, respectively. 48 Distinguishing severe stages (F3–F4) from low or moderate stages (F0–F2) of fibrosis with high FIB-4 scores (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In Mahassadi's study [11] in Côte d'Ivoire, the average APRI score was 0.72 (IQR = 0.4-1.85). For Bonnard [12] in Burkina Faso, with an APRI score threshold value of 1.0, significant fibrosis could be correctly predicted with a sensitivity of 55% and a specificity of 50%.…”
Section: The Apri Scorementioning
confidence: 95%
“…If the reference examination remains hepatic biopsy, its invasiveness, high cost and inconsistent acceptability by patients, have motivated the development of new methods of evaluating fibrosis, called « non-invasive » tests. Many studies [4][5][6][7][8][9][10] including a few african studies [11,12] have led to proposing and then validating noninvasive tests capable of replacing liver biopsy to estimate the degree of fibrosis in patients with chronic hepatitis B and C viruses. In Togo, the prevalence of hepatits B virus (HBV) varies between 5% and 16.4% [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The AUC of the AAR, AP and APRI index for predicting cirrhosis were respectively 0.555, 0.652 and 0.761. They concluded that these indices are good as noninvasive laboratory tests to predict cirrhosis in patients with HCV (Fujii et al, 2009 (Mahassadi et al, 2010). Kim determined the clinical performances of AAR, AP and APRI index for the prediction of liver fibrosis in chronic viral liver diseases in 225 patients with chronic viral liver diseases (180 with hepatitis B virus, 43 with hepatitis C virus, and 2 with hepatitis B+C virus) that underwent a liver biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%